2019
DOI: 10.30997/jag.v5i2.2314
|View full text |Cite
|
Sign up to set email alerts
|

Respon Pertumbuhan Aksesi Kemangi Pada Berbagai Komposisi Pupuk Nitrogen Alami

Abstract: Basil is not only useful as a vegetable, but also has many medicinal properties. This encourages thedevelopment of environmentally friendly basil cultivation, through the use of natural fertilizers.This study aims to determine the response of various basil accessions to the composition of sourceN fertilizer derived from cow urine, kipahit (Tithonia) compost and Urea. The study was conductedwith a factorial completely randomized design. The first factor is the accession of basil, namelyKemang, Ciaruten, Cijujug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
0
1
0
Order By: Relevance
“…Analysis of organic fertilizers showed that Mexican sunflower compost contained N of 2.69%, P2O5 0.99%, and K2O 4.96%. The products are relatively low compared to the previous study [18] that N content of Mexican sunflower compost is 3.90%, and Lestari [14] that Mexican sunflower contains 3.50-4.00% N, 0.35-0.38% P, 3.50-4.10% K. The total N content in compost has decreased because composting for 25-30 days with materials that have a high N content [19].…”
Section: Soil Analysis and Organic Fertilizermentioning
confidence: 87%
“…Analysis of organic fertilizers showed that Mexican sunflower compost contained N of 2.69%, P2O5 0.99%, and K2O 4.96%. The products are relatively low compared to the previous study [18] that N content of Mexican sunflower compost is 3.90%, and Lestari [14] that Mexican sunflower contains 3.50-4.00% N, 0.35-0.38% P, 3.50-4.10% K. The total N content in compost has decreased because composting for 25-30 days with materials that have a high N content [19].…”
Section: Soil Analysis and Organic Fertilizermentioning
confidence: 87%
“…Menurut Gottimukkala et al (2019) Pemberian komposisi pupuk 75% N-Urea + 25% N-kompos kipahit juga menghasilkan jumlah tunas, panjang tunas total dan bobot basah dan kering panen setara dengan yang diberi 25% N-Urea + 75% N-urine sapi. Hal ini menunjukkan kemampuan kompos kipahit untuk menyediakan hara, terutama N, karena kandungan Nnya relatif tinggi, sebesar 3,76% (Rahayu et al 2021). walaupun dengan dengan porsi Urea yang lebih tinggi dibandingkan dengan urine sapi.…”
Section: Pembahasanunclassified
“…Diketahui penanaman secara anorganik dapat memiliki efek samping jika hasil pertaniannya dikonsumsi dalam jangka waktu yang panjang akibat residu kimia yang dimiliki pupuk anorganik, banyaknya penggunaan pestisida dan pupuk kimia sintetik secara terus menerus dalam jangka waktu yang panjang pada budidaya tanaman kemangi akan berdampak pada kesehatan konsumennya bahkan mampu mengubah kesuburan tanah tempat budidaya [6]. Selain itu, dikarenakan efektivitas penggunaan pupuk urea tidak bertahan lama maka pupuk urea digunakan secara berulang-ulang yang membuatnya menyebabkan perubahan struktur tanah, pemadatan, serta membuat kandungan unsur hara dalam tanah menurun dan mengalami pencemaran tanah.…”
Section: Pendahuluanunclassified